Development of Virtual Reality Learning Media Assisted by Millealab for Islamic History Education in Secondary School - Pandu Hyangsewu; Muhamad Ridwan Sudaryat; Achmad Faqihuddin; Aulia Tegar Wicaksono; Rosmalizawati Ab Rashid (Information Technology Education Journal, 2026)
Purpose – This study aims to develop and test the feasibility and practicality of a virtual tour learning media assisted by the Millealab platform for Islamic history material on the Ottoman Empire at one of the SMP in Bandung. Design/methods/approach – This study uses a Research and Development (R&D) design through the procedural ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). Sampling was conducted using a random sampling technique involving 167 students for needs analysis and 30 students for field implementation. Data collection instruments included expert validation sheets and practicality assessment questionnaires. Findings – The results showed that the virtual tour product achieved "Highly Valid" criteria with scores of 89.50% from material experts and 92.30% from media experts. Field trials recorded "Highly Practical" criteria with 88.00% from educators and 88.40% from students Research implications/limitations – The scope of this study is strictly limited to the Ottoman Empire material and small-scale practicality testing. Functionally, this innovation is proven to bridge the technical barriers of educators in producing virtual reality content without requiring programming skills. Originality/value – This research provides a practical framework regarding the utilization of a no-code virtual reality platform within the domain of Islamic history education, an area that is still rarely examined operationally.